A Patient-Reported Outcome Based Comparison of Cheilectomy with and without Proximal Phalangeal Dorsiflexion Osteotomy for Hallux Rigidus. Issue 4 (November 2022) - Mizher, Rami; Fuller, Robert; Kim, Jaeyoung; Rajan, Lavan; Cororaton, Agnes D.; Kumar, Prashanth; An, Tonya W.; Deland, Jonathan T.; Ellis, Scott J.
Category: Midfoot/Forefoot Introduction/Purpose: Cheilectomy with and without Moberg osteotomy is used to improve function and remove pain in early- moderate stage hallux rigidus. The rise of patient-reported outcome measurements allows greater precision in comparing treatments as value-driven paradigms become increasingly important in clinical decision-making. This study provides the first comparison of patient-reported outcomes between isolated cheilectomy (C) and cheilectomy with Moberg (CM) osteotomy for hallux rigidus. We compared one and two-year PROM scores between patients who underwent C and CM for hallux rigidus using PROMIS, a validated patient-reported outcomes measurement system, and compared rates of complications and subsequent operations between the two groups. We hypothesized that patients who underwent CM would experience better clinical outcomes and fewer returns to the operating room than patients undergoing cheilectomy alone. Methods: A single-center, retrospective registry search identified all patients with preoperative PROMIS scores who underwent cheilectomy, with and without concomitant proximal phalangeal dorsiflexion osteotomy, for hallux rigidus between January 2016 and December 2020. An a priori power analysis determined that 24 patients per cohort were needed to detect a previously published minimum clinically important difference of 5.8 points on the PROMIS Physical Function scale with alpha = .05 and 80% power. However, all C patients were included. Because there were far fewer isolated cheilectomies (62), all C patients were compared with a commensurate number of consecutive CM cases (67) using preoperative, one-year, and two-year PROMIS scores for Physical Function, Pain Interference, Pain Intensity, Global Physical Health, Global Mental Health, and Depression, as well as complication and revision data from chart review. Age, sex, BMI, preoperative radiographic hallux rigidus grade, and preoperative range of motion were compared between the two cohorts. Results: PROMIS outcome data is given in Table 1. Both groups demonstrated statistically significant improvements in PROMIS Physical Function, Pain Interference, Pain Intensity, and Global Physical Health (P <.001 for all, both preoperative to one-year and preoperative to two-year), but not Global Mental Health or Depression. There were no differences between groups among the demographic and preoperative variables compared. The CM cohort reported worse Pain Interference scores preoperatively (58.1+- 5.9 vs. 52.4 +- 7.01, P < .001) and at one year (50.0 +- 9.3 vs. 45.1 +- 9.8, P = .01), while the C cohort reported worse Pain Intensity scores preoperatively (55.6 +- 7.3 vs. 49.6 +- 6.8, P < .001) and at one year (45.9 +- 8.0 vs. 39.9 +- 8.2, P < .001). These differences were no longer significant at two years postoperatively. There were no statistically significant differences between cohorts for additional PROMIS scores or complications data. Conclusion: The addition of a Moberg osteotomy does not appear to significantly change short-medium term outcomes of cheilectomy for hallux rigidus treatment. Our data contradicts the notion that addition of a Moberg osteotomy increases the likelihood of postoperative complications. The overall good results found for both procedures, as well as the general similarity between outcomes between them, suggest that external considerations like recovery time, comfort level with a more invasive osteotomy, and overall goals with surgery may be of greater importance than short-term clinical outcomes when deciding on the appropriate course of treatment for a given patient.